(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2013)
The traditional practice of post operative starvation after gut resection and primary anastomosis has been recently challenged. Contrary to wide spread opinion, evidence from clinical studies suggest that initiating feeding early is advantageous in postoperative patients. Various clinical trials have shown that early enteral feeding helps in the reduction of post operative ileus, anxiety and hospital stay. The purpose of this study was to compare the effects of early and traditional feeding, and was conducted among patients who underwent gut resection and primary end to end anastomosis. The study population (n=50) was divided into two arms. Arm-A (n=25) was given feeding after passage of flatus, stool when bowel sound was present, usually within second to fourth post operative day. Arm-B (n=25) was given early enteral feeding, started within 16-24 hours, in the first Post operative day (POD) after removal of the naso gastric tube. There were no statistically significant variations in age, sex, bodyweight, average hemoglobin level, antibiotics, and suture materials used in both arms. Post operative hospital stay was 9.09 days in Arm-A and 5.42 days in Arm-B. It was significantly low (P < 0.05) in Arm-B. The complications after operation were also low in Arm-B. Early enteral feeding can help to decrease the negative impact of the metabolic response to injury. It also stimulates restoration of the barrier functions of the intestine, improve the return of the functions and reduce the duration of post operative ileus and hence reduce the risk of serious complications. DOI: http://dx.doi.org/10.3329/jpsb.v2i1.15142 Journal of Paediatric Surgeons of Bangladesh (2011) Vol. 2 (1): 7-11